The medial olivocochlear reflex strength is modulated during a visual working memory task - Marcenaro, Bruno; Leiva, Alexis; Dragicevic, Constantino; López, Vladimir; Delano, Paul H. (Journal of neurophysiology, 2021)
The auditory efferent system has been proposed to function as a biological filter of cochlear responses during selective attention. Here, we recorded electroencephalographic activity and otoacoustic emissions in response to auditory distractors during a visual working memory task in humans. We found that the olivocochlear efferent activity is modulated during the visual working memory period suggesting a common mechanism for suppressing cochlear responses during selective attention and working memory. Top-down modulation of sensory responses to distracting stimuli by selective attention has been proposed as an important mechanism by which our brain can maintain relevant information during working memory tasks. Previous works in visual working memory (VWM) have reported modulation of neural responses to distracting sounds at different levels of the central auditory pathways. Whether these modulations occur also at the level of the auditory receptor is unknown. Here, we hypothesize that cochlear responses to irrelevant auditory stimuli can be modulated by the medial olivocochlear system during VWM. Twenty-one subjects (13 males, mean age 25.3 yr) with normal hearing performed a visual change detection task with different VWM load conditions (high load = 4 visual objects; low load = 2 visual objects). Auditory stimuli were presented as distractors and allowed the measurement of distortion product otoacoustic emissions (DPOAEs) and scalp auditory evoked potentials. In addition, the medial olivocochlear reflex strength was evaluated by adding contralateral acoustic stimulation. We found larger contralateral acoustic suppression of DPOAEs during the visual working memory period ( n = 21) compared with control experiments ( n = 10), in which individuals were passively exposed to the same experimental conditions. These results show that during the visual working memory period there is a modulation of the medial olivocochlear reflex strength, suggesting a possible common mechanism for top-down filtering of auditory responses during cognitive processes. NEW & NOTEWORTHY The auditory efferent system has been proposed to function as a biological filter of cochlear responses during selective attention. Here, we recorded electroencephalographic activity and otoacoustic emissions in response to auditory distractors during a visual working memory task in humans. We found that the olivocochlear efferent activity is modulated during the visual working memory period suggesting a common mechanism for suppressing cochlear responses during selective attention and working memory.